Policy Design for Electronic Business License in Cimahi City (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
The Online Single Submission System, or OSS, is an electronically integrated investment and business licensing acceleration service in Indonesia. Online Single Submission – Risk-Based Approach is designed to simplify and improve the efficiency of the business licensing process with a risk-based approach. This policy aims to enhance the ease of doing business and regional competitiveness by integrating the electronic licensing system. The purpose of this study is to provide policy recommendations on implementing risk-based electronic business licensing from the perspective of experts in Cimahi City. The methodology employed in this study is qualitative, involving the analysis of problem tree mapping and the weighting of Expert Respondents' Perceptions for alternative policy development. The implementation of electronic business licensing in Cimahi City has been carried out by Government Regulation Number 5 of 2021. The effectiveness of implementing OSS-RBA in Cimahi City can be achieved by overcoming the main problem, which is related to the service accuracy criteria. The recommended alternative solution is the development of a policy to encourage the creation of a Detailed Spatial Plan that is integrated with SiPinter's OSS digitally. Another alternative solution recommendation is the development of coordination regulations between the Central Government and Regional Governments in the planning of national strategic projects, aiming to achieve a harmonious Agreement on the Suitability of Space Utilisation Activities.